Psychological Analysis of the Main Character as Influenced by External Conflicts in the Movie Entitled “Gone Girl” - Sain, Sukmawati; Resen, I Wayan; Santika, I Dewa Ayu Devi Maharani (Journal of Language and Applied Linguistics, 2023)
This study entitled “Psychological Analysis of The Main Character as Influenced by External Conflicts in the Movie Entitled “Gone Girl”. It is focused on psychological condition of the character as influenced by external conflicts. The aims of this study are to find out the types of external conflicts faced by the main character and to analyze the effect of those external conflicts that the main character faced to her psychological condition as found in the movie entitled “Gone Girl”. This study used theories from Stantont (1956) and Koesnosoebroto (1988) to find out the types of external conflicts and Bernhardt (1953) to analyze the psychological aspect of the main character. Descriptive and qualitative methods were used to analyze the data while observation methods were used to collect the data. The result found that there are 33 external conflicts and 16 internal conflicts faced by the character and in this study the writer will focused on analyzing the external conflicts faced by the main character in Gone Girl movie that influenced her psychological condition.